KOMPARATIF HUKUM ACARA PIDANA POSITIF DAN HUKUM ACARA PIDANA ISLAM (JINAYAH) ACEH DALAM PROSES PENYIDIKAN - Dahyul Daipon (INSTITUT AGAMA ISLAM NEGERI PALANGKA RAYA, 2020)
AbstractThis research aims to examine the differences of investigation process between the book of Procedural Criminal Law Constitution (KUHAP) or the Constitution number 8 of 1981 about Positive Procedural Criminal Law and Qanun Aceh number 7 of 2013 about Jinayat Procedural Law. The method used is the yuridis normative law research method. The Identification of problem is How is the investigation process based on the book of Procedural Criminal Law Constitution (KUHAP)? How is the investigation process based on Qonun Aceh number 7 of 2013 about Jinayat Procedural Law? What is the differences of investigation process based on Positive Procedural Criminal Law and Qanun Aceh number 7 of 2013 about Jinayat Procedural Law? The Result of analysis is Investigation process in KUHAP starts of the Investigation. Enforcement, Examination, Settlement, and Submition the case file to the public presecutor, it is process of investigation that written in the Constutition number 7 of 2013 about Jinayat Procedural Law. It mentions in verse 110 until 132. The differences of investigation process based on Positive Procedural Criminal Law and Qanun Aceh number 7 of 2013 about Jinayat Procedural Law are (1)related to paradigms of investigation description that different managed, (2) related to the investigator authority, and (3) related to the direct investigation of crime/jarimah. AbstrakTujuan penelitian ini ialah untuk mengkaji perbedaan proses penyidikan antara Kitab Undang-Undang Hukum Acara Pidana (KUHAP) atau Undang-Undang nomor 8 tahun 1981 tentang Hukum Acara Pidana Positif dengan Qonun Aceh Nomor 7 Tahun 2013 Tentang Hukum Acara Jinayat. Adapun metode yang digunakan ialah metode penelitian hukum normatif yuridis (yuridis normative). Rumusan masalahnya ialah Bagaimana Proses Penyidikan menurut Kitab Undang-Undang Hukum Acara Pidana (KUHAP)? Bagaimana Proses Penyidikan menurut Qonun Aceh Nomor 7 Tahun 2013 Tentang Hukum Acara Jinayat? Apa Perbedaan Proses Penyidikan menurut Hukum Acara Pidana Positif dan Qonun Aceh Nomor 7 Tahun 2013 Tentang Hukum Acara Jinayat? Adapun hasil dan pembahasannya ialah Proses Penyidikan menurut KUHAP ialah mulai dari Penyelidikan. Penindakan, Pemeriksaan, Penyelesaian dan serta penyerahan berkas perkara kepada Jaksa Penuntut Umum, Bahwa proses Penyidikan yang tercatum di dalam Undang-undang Nomor 7 Tahun 2013 Tentang Hukum Acara Jinayat ialah tercantum di dalam Pasal 110 sampai dengan Pasal 132. Adapun terkait Perbedaan Proses Penyidikan menurut Hukum Acara Pidana Positif dan Qanun Aceh Nomor 7 Tahun 2013 Tentang Hukum Acara Jinayat ialah (1) terkait tentang paradigma penjelasan penyidikan yang diatur berbeda, (2) terkait tentang wewenang penyidik dan (3) terkait dengan penyidikan langsung tindak pidana/jarimah.Kata Kunci: Proses, Penyidikan, Qonun, Aceh,